Bullying at 8 years and violent offenses by 31 years: the Finnish nationwide 1981 birth cohort study - Tiiri Elina; Uotila Jaakko; Elonheimo Henrik; Sillanmäki Lauri; Klomek Anat Brunstein; Sourander Andre (SPRINGER, 2022)
This study explored the associations between bullying perpetration and victimization at 8 years of age and violent offenses by the age of 31. Data were obtained for subjects enrolled in a population-based longitudinal birth cohort study. In 1989, 5813 8-year-old children (attrition 3.4%), and their parents and teachers, were surveyed about bullying. When 5405 subjects (attrition 10.2%) were 15-31 years of age, violent offenses were extracted from the Finnish National Police Register. We analyzed the data by sex and categorized bullying perpetration and victimization by frequency. Violent offenses were categorized by severity. Cox regression analyses estimated the hazard ratios (HRs) and 95% confidence intervals (95% CIs). When they were compared to males who had not been bullies at 8 years of age, frequent male bullies had an increased hazard for violent offenses (adjusted HR 3.01, 95% CI 2.11-4.33) and severe violent offenses (adjusted HR 2.86, 95% CI 1.07-7.59) as adults, even when the data were controlled for them being victims, parental education level, family structure and child psychopathology. Frequent female bullies also had an increased hazard for violent offenses, compared to those who had not bullied others (adjusted HR 5.27, 95% CI 1.51-18.40). Frequent male bullying was associated with higher odds for violent offenses compared to only bullying sometimes. Being a victim was not associated with violent offenses. Preventing childhood bullying could reduce violent offenses by both sexes.